Encephalomyelitis Caused by Balamuthia mandrillaris in a Woman With Breast Cancer: A Case Report and Review of the Literature - Hu, Juan; Zhang, Yiqi; Yu, Yongwei; Yu, Huili; Guo, Siruo; Shi, Ding; He, Jianqin; Hu, Chi; Yang, Jiqi; Fang, Xueling; Xiao, Yonghong (Frontiers in Immunology, 2022)
Balamuthia mandrillaris is one cause of a rare and severe brain infection called granulomatous amoebic encephalitis (GAE), which has a mortality rate of >90%. Diagnosis of Balamuthia GAE is difficult because symptoms are non-specific. Here, we report a case of Balamuthia amoebic encephalomyelitis (encephalitis and myelitis) in a woman with breast cancer. She sustained trauma near a garbage dump 2 years ago and subsequently developed a skin lesion with a Mycobacterium abscessus infection. She experienced dizziness, lethargy, nausea and vomiting, inability to walk, and deterioration of consciousness. Next-generation sequencing of cerebrospinal fluid (CSF) samples revealed B. mandrillaris, and MRI of both brain and spinal cord showed abnormal signals. T-cell receptor (TCR) sequencing of the CSF identified the Top1 TCR. A combination of amphotericin B, flucytosine, fluconazole, sulfamethoxazole, trimethoprim, clarithromycin, pentamidine, and miltefosine was administrated, but she deteriorated gradually and died on day 27 post-admission.